Reinstatement of Centaurea cyanomorpha (Asteraceae), an endemic species from Southeastern Bulgaria - Stoyanov, Stoyan S. (Phytotaxa, 2016)
Centaurea cyanomorpha, so far known only from a single plant collected in May 1926, was rediscovered and studied at its locus classicus Kara Bair, near the town of Topolovgrad (SE Bulgaria). Its taxonomic status varied in times and remained hitherto uncertain. The species has been treated as a synonym of C. pseudaxillaris, C. napulifera and C. depressa. However, a detailed examination of the type specimen and plants from the type locality, as well as additional plants from different localities indicate that C. cyanomorpha is a clearly distinct taxon and should be maintained as a separate species. Cyanus diospolitanus (≡ Centaurea diospolitana), recently described from Derventski Hills, Yambol Province (SE Bulgaria), has turned out to be identical to C. cyanomorpha and should be treated as a later heterotypic synonym of the latter. Comparisons of the key morphological characters of the close relatives C. cyanomorpha and C. pseudaxillaris and maps of their distributions are given. A new combination, Cyanus cyanomorphus comb. nov., is provided.